A global database of soil microbial phospholipid fatty acids and enzyme activities - van Galen, Laura G.; Smith, Gabriel Reuben; Margenot, Andrew J.; Waldrop, Mark P.; Crowther, Thomas W.; Peay, Kabir G.; Jackson, Robert B.; Yu, Kailiang; Abrahão, Anna; Ahmed, Talaat A.; Alatalo, Juha M.; Anslan, Sten; et al. (Springer Nature, 2025)
Soil microbes drive ecosystem function and play a critical role in how ecosystems respond to global change. Research surrounding soil microbial communities has rapidly increased in recent decades, and substantial data relating to phospholipid fatty acids (PLFAs) and potential enzyme activity have been collected and analysed. However, studies have mostly been restricted to local and regional scales, and their accuracy and usefulness are limited by the extent of accessible data. Here we aim to improve data availability by collating a global database of soil PLFA and potential enzyme activity measurements from 12,258 georeferenced samples located across all continents, 5.1% of which have not previously been published. The database contains data relating to 113 PLFAs and 26 enzyme activities, and includes metadata such as sampling date, sample depth, and soil pH, total carbon, and total nitrogen. This database will help researchers in conducting both global- and local-scale studies to better understand soil microbial biomass and function.
Keywords: microbial communities; microbial ecology; microbiology techniques